15. STATUS OF PARTICIPATION, KNOWLEDGE ABOUT HIV INFECTION PRE-EXPOSITION PROPHYLAXIS AND SOME RELATED FACTORS OF MEN WHO HAVE SEX WITH MEN IN NINH KIEU DISTRICT, CAN THO CITY, 2023 (Vietnam Journal of Community Medicine, 2024)
Overview: Men who have sex with men are at the highest risk of HIV infection in recent years. Pre-exposure prophylaxis treatment connection is considered a solution in the prevention of HIV infection.Objectives: To determine the rate of pre-exposure prophylaxis, the knowledge of the subject pre-exposure prophylaxis and some factors related to participating in pre-exposure protection treatment of men who have sex with men in Ninh Kieu district, Can Tho city, 2023.Method: A cross-sectional study in 400 cases were men who have sex with men from April 2023 to October 2023. The data were collected by questionaires. SPSS 18.0 software was used for analyzing data. Analyze factors associated by using c2 test, univariate.Results: The rate of participation in pre-exposure prophylaxis treatment is 37.3%. The general knowledge reached 79,3%. Some related factors were: number of sexual partners, safe sex, fear of discrimination, come out, general knowledge with p < 0.05.Conclusion: The proportion of participating in pre-exposure protection treatment is quite low. It is necessary to focus on appropriate health education communication measures, increase knowledge and raise people’s awareness, especially for men who have sex with men.
Keywords: Men who have sex with men; pre-exposure prophylaxis; knowledge